RECONSTRUCTING PATERNITY LEAVE RIGHTS FROM A HUMAN RIGHTS PERSPECTIVE - Frida Tri Utami (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The transformation of work–family relations in modern societies has generated a growing demand for labor regulations that are more responsive to the role of fathers in childcare. Within the current framework of labor law practice, the right to paternity leave for male workers remains subject to limited legal protection and has not fully reflected human rights principles, particularly those related to gender equality and the protection of family life. This study aims to examine the legal status and regulatory framework of paternity leave within the labor law system and to assess the quality of its protection from a human rights perspective following recent regulatory developments in the field of family welfare. The research employs a normative legal method using statutory and conceptual approaches. The legal materials analyzed include national legislation, international human rights instruments, as well as relevant legal doctrines and scholarly studies. The analysis reveals that although there is normative recognition of the father’s role within the family, the regulation of paternity leave remains minimal and fails to provide substantive legal protection, particularly in terms of leave duration and certainty of implementation. This situation indicates a tension between the state’s normative commitment to family rights and the practical reality of legal protection within employment relations. The study concludes that paternity leave should be understood as an integral component of social and family rights with a human rights dimension, thereby requiring strengthened regulation to effectively address the demands of gender equality and work–family balance.